Risks of Educational Inclusion: The Experience of Regional Studies in Tyumen State University - Volosnikova L.M.,; Efimova G.Z.,; Ogorodnova O.V., (Психологическая наука и образование, 2017)
The paper presents the results of sociological research in the universities of the Tyumen Province, Russia (2081 questionnaires from 9 state institutions of higher education, 2016, April). In the paper, we consider only one aspect of inclusion, namely, joint training of healthy students and students with disabilities. The aim of the study is to assess the risks of inclusive education and its risk factors. Inclusive education is interpreted as 1) a social value, 2) an alternative to social exclusion 3) a resource for development, and 4) an educational innovation with risk potential. The authors developed the concept of «risk» and «risk-factor» for inclusive education, offering their classification. The responses is structured and grouped into three risks mega-groups: 1) general social risks, 2) institutional and group risks, and 3) risks for education actors. These include the risks of falling quality of general, tertiary and vocational education, the risks of social dependency, organizational risks, threat of simulation inclusion and the formal inclusion, personal and professional risks of students, teachers, parents and administrators. Insufficient level of inclusive educational environments in institutions of general, vocational and higher education, lack of skills and competences of teachers for inclusive education, the deficit tolerant attitudes towards persons with disabilities in society and school class are all identified as risk factors. The research leads to conclusions about the need for a conscious administrative influence on the factors to overcome their negative consequences for the success of inclusion. This work was supported by grant 543873-TEMPUS-1-2013-1-DE-TEMPUS-JPCR.